Analisis Sifat Mekanik Komposit Tangkai Ilalang Bermatriks Polyester Terhadap Pengujian Lentur - Pratama, Adi; Yuliyanto, Yuliyanto; Subhan, Muhammad (Manutech : Jurnal Teknologi Manufaktur, 2025)
The use of metal materials in the industrial world is increasingly widespread, so that over time metals are becoming increasingly difficult to obtain and people are required to think critically so they can look for alternative materials from the limitations of metals that are easily available and abundant, one of which is composite materials. Composite is a combination of two or more materials with different ingredients. The aim of this research was to determine the effect of thatch stalk length of 50, 60, 70 mm and a volume fraction of 35% with an oven temperature of 90°C for 45 minutes, 40% with an oven temperature of 100°C for 45 minutes, and 45% with an oven temperature of 110°C for 45 minutes when soaking the thatch stalks in 4% NaOH for 2 hours for the bending test. The highest flexural strength value was at a shank length of 50 mm with a volume fraction of 35% with an oven temperature of 90°C of 48.23 MPa. This is because the shorter the thatch stalks, the denser the thatch stalk composite looks and at a volume fraction of 35% the thatch stalks and resin stick well and the oven temperature should not exceed 90°C because if it exceeds the thatch stalks it will shrink and the flexural strength will increase. small.